Selective synthesis of pyridyl pyridones and oxydipyridines by transition-metal-free hydroxylation and arylation of 2-fluoropyridine derivatives. Issue 6 (28th January 2020) - Liao, Chunshu; Li, Jianrong; Chen, Xiaoqiong; Lu, Jingjun; Liu, Qiang; Chen, Lu; Huang, Yubing; Li, Yibiao
Abstract : A transition-metal-free protocol for selective synthesis of various pyridyl pyridones and oxydipyridines through hydroxylation and arylation of 2-fluoropyridines has been described. Abstract : An efficient protocol for the construction of various pyridyl pyridone and oxydipyridine derivatives through a hydroxylation and arylation tandem reaction of 2-fluoropyridines is reported. Under simple transition-metal-free conditions, the reaction provided a series of products in good to excellent yields, and their structures were confirmed by crystal diffraction analysis. Furthermore, the controlling effect of 6-position substituents on the highly selective synthesis of pyridone and oxydipyridine was studied.